A novel consequent‐pole bearingless PMSM with integrated winding for flywheel energy storage - Xu, Jie; Sun, Yukun; Yuan, Ye; Huang, Yonghong; Yang, Fan (Electronics letters, 2021)
Generating torque and suspension force with one set of windings at the same time can increase the copper space factor and improve the torque output capacity. This structure has a unique application advantage for bearingless motors used in onboard flywheel energy storage. A consequent‐pole bearingless permanent magnet synchronous motor (PMSM) with integrated winding is designed and researched. Regulating suspension current has minimal effect on the torque performance of the motor in this design. The effectiveness and feasibility of this design are verified through a finite element calculation. Its advantages and application scope are discussed.